Differential diagnosis of adnexal masses: risk of malignancy index, ultrasonography, magnetic resonance imaging, and radioimmunoscintigraphy. Issue 1 (1st January 2007) - Van Trappen, P. O.; Rufford, B. D.; Mills, T. D.; Sohaib, S. A.; Webb, J. A.W.; Sahdev, A.; Carroll, M. J.; Britton, K. E.; Reznek, R. H.; Jacobs, I. J.
Abstract : A risk of malignancy index (RMI), based on menopausal status, ultrasound (US) findings, and serum CA125, has previously been described and validated in the primary evaluation of women with adnexal masses and is widely used in selective referral of women from local cancer units to specialized cancer centers. Additional imaging modalities could be useful for further characterization of adnexal masses in this group of women. A prospective cohort study was conducted of 196 women with an adnexal mass referred to a teaching hospital for diagnosis and management. Follow-up data was obtained for 180 women; 119 women had benign and 61 women malignant adnexal masses. The sensitivity and specificity of specialist US, magnetic resonance imaging (MRI), radioimmunoscintigraphy (RS), and the RMI were determined. We identified a subgroup of women with RMI values of 25–1000 where the value of further specialist imaging was evaluated. Sensitivity and specificity for specialist US were 100% and 57%, for MRI 92% and 86%, and for RS 76% and 87%, respectively. Analysis of 123 patients managed sequentially, using RMI cutoff values of ≥25 and <1000 and then US and MRI provided a sensitivity of 94% and a specificity of 90%. Using this RMI cutoff followed by specialist US and MRI, as opposed to the traditional RMI cutoff value of 250, can increase the proportion of patients with cancer appropriately referred in to a cancer center, with no change in the proportion of patients with benign disease being managed in a local unit